A method for evaluating the risks of glucose dysregulation in daily life by continuous measurement of glucose excursions under reduced glycemic load: a pilot study - Katagiri, Yoshitada; Ozaku, Hiromi; Kondo, Katsuhiko (Frontiers in Sensors, 2024)
Continuous glucose monitoring is essential for the management of patients with metabolic syndromes in their daily lives. However, how metabolic risks are accessed using time-series glucose excursion data for healthy individuals remains unclear. Thus, this study aimed to present a method for evaluating the risks of glucose dysregulation by analyzing glucose responses under reduced glycemic load using a phytochemical alpha-glucosidase inhibitor. A 14-day pilot trial with healthy adult participants was conducted to demonstrate the validity of the method. The results showed that ultradian glucose spike packets with lower heights dominantly appeared under reduced glycemic load, replacing postprandial single-lobe glucose spikes with higher heights. Furthermore, the frequency dominance of ultradian spike packets contributed to the reduction of overall mean glucose excursions during the test period under reduced glycemic load. Based on the time-delay model, it was indicated that glycemic load reduction recovers regular glucose–insulin coupling accompanying ultradian oscillations, thereby contributing to the maintenance of glucose homeostasis. The findings of this study indicate that the frequency ratio between pulsatile spike packets and single-lobe spikes could be a marker for evaluating glucose regulation/dysregulation in healthy adults.